A self-repairing anti-corrosion coating and its preparation method and application

By using self-repair and anticorrosion coating composed of two-dimensional nanosheets, polyphenol bio-based materials, etc., the problems of complex process, high cost and difficult performance coordination in the existing technology are solved, and a high environmentally friendly, economical and efficient self-repair effect is achieved, and the comprehensive performance of the surface protective layer of metal materials is improved.

CN119039861BActive Publication Date: 2025-03-25SHANGHAI HILONG SHINE NEW MATERIAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411507145.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-03-25
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing self-repair anti-corrosion coatings are difficult to achieve environmentally friendly, economical and efficient self-repair effects due to the complexity of process, high cost, difficulty in coordination with anti-corrosion and self-repair performance, poor compatibility and great influence of mechanical properties.

Method used

A self-healing anticorrosion coating consisting of two-dimensional nanosheets, polyphenol bio-based materials, polyolefin alcohols, polymer resins containing active hydrogen atoms and isocyanate curing agents are used to form a coating with gel microspheres evenly distributed inside by preparing nanosheets water sol, emulsification, freezing and thawing.

Benefits of technology

It has achieved a self-repair anti-corrosion coating with high environmental protection, small mechanical performance loss of coating, good shielding performance and strong self-repair performance, which has improved the anti-corrosion, anti-fouling and self-repair performance of the surface protective layer of metal materials and extended its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039861B_ABST
    Figure CN119039861B_ABST
Patent Text Reader

Abstract

The present invention provides a self-repairing anti-corrosion coating and a preparation method and application thereof, and relates to the technical field of protective coatings. The self-repairing coating comprises: two-dimensional nanosheets, polyphenolic bio-based materials, polyolefin alcohol, polymer resin containing active hydrogen atoms, isocyanate curing agent and dispersion medium. The preparation method of the self-repairing coating of the present invention first forms a nanosheet hydrosol with two-dimensional nanosheets, polyphenolic bio-based materials and polyolefin alcohol, and then forms uniformly distributed gel microspheres in the polymer resin containing active hydrogen atoms through emulsification and freeze-thaw action, and then mixes the polymer resin with the isocyanate curing agent to obtain a self-repairing coating. The self-repairing coating of the present invention has the advantages of simple preparation, high environmental protection, small loss of mechanical properties of the coating, good shielding performance, strong self-repairing performance, and also has good anti-corrosion and anti-fouling properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of protective coatings, and in particular to a self-repairing anti-corrosion coating and a preparation method and application thereof. Background Art

[0002] Metal materials have become an indispensable component in infrastructure and other fields due to their excellent material strength and characteristics. However, metal materials are prone to corrosion due to their use in a variety of complex environments. Corrosion not only affects the appearance of metal materials, but also weakens their functional properties such as strength and toughness, posing a continuous threat to the safety and normal operation of structural facilities.

[0003] Although the corrosion of metal materials cannot be completely avoided, taking certain protective measures can delay the occurrence of corrosion, reduce the corrosion rate, and reduce the harm caused by corrosion. Among them, the construction of anti-corrosion coatings on metal surfaces can effectively block the penetration of corrosive media in the environment. The method is simple and has been widely used. However, during the protection process, the anti-corrosion coating will be affected by its own film formation and external environmental factors (such as salt spray, ultraviolet rays, corrosive media, etc.), resulting in defects such as micropores or microcracks in the coating, generating corrosion channels, and reducing the protective performance of the coating.

[0004] Traditional coating technology is difficult to repair these defects without external intervention, resulting in loss of anti-corrosion protection. To overcome these limitations, inspired by organisms in nature, it was found that some organisms can achieve self-protection by repairing damaged shells or healing skin wounds. Smart anti-corrosion coatings are material technologies that can autonomously repair themselves in response to environmental stimuli. They have a healing mechanism for defects or corrosion with minimal human intervention, and can actively fill these defects and enhance their ability to resist corrosion. Through this process, the coating can effectively prevent cathode and anode reactions during corrosion and reduce the corrosion rate. Among them, microcapsule repair is a common method for preparing smart self-healing coatings. These microcapsules store corrosion inhibitors and repair agents. When the coating is stimulated by external stimuli or corroded, the corrosion inhibitors or repair agents inside the microcapsules will be released to repair the damaged parts of the coating, so that the coating regains its anti-corrosion properties. This process significantly improves the overall performance and service life of the coating.

[0005] Existing self-healing anti-corrosion coatings have great application prospects in the field of metal corrosion protection due to their superior functionality. However, green, environmentally friendly, high-performance self-healing anti-corrosion coatings still face certain challenges, such as:

[0006] (1) The process of preparing self-healing microcapsule materials is complicated, and the cost of industrial application is high, which is not conducive to actual large-scale application;

[0007] (2) It is still difficult to coordinate the barrier properties and self-healing ability of the anti-corrosion coating. The introduction of self-healing materials (such as microcapsules, etc.) has a great impact on the density of the coating. In addition, some materials are hydrophilic, which affects the initial anti-corrosion performance of the anti-corrosion coating.

[0008] (3) The compatibility of the introduced self-healing materials in the anti-corrosion coating is challenging and there is a risk of phase separation. In addition, there are differences in the structural strength of the self-healing materials, which has a significant impact on the mechanical properties of the prepared self-healing anti-corrosion coating, affecting the long-term use of the anti-corrosion coating.

[0009] Therefore, it has become necessary and urgent to research and develop a self-repairing coating for metal materials that is environmentally friendly, economical, highly efficient, and can quickly self-repair, and that can improve the coating's anti-corrosion performance, anti-fouling performance, self-repairing performance, and service life without affecting the comprehensive performance of the original coating system.

[0010] In view of this, the present invention is proposed. Summary of the invention

[0011] The first purpose of the present invention is to provide a self-repairing anti-corrosion coating, which has the advantages of high environmental protection, small loss of coating mechanical properties, good shielding performance, strong self-repairing performance, and also has good anti-corrosion and anti-fouling properties.

[0012] The second object of the present invention is to provide a method for preparing a self-repairing anti-corrosion coating.

[0013] The third purpose of the present invention is to provide an application of a self-repairing anti-corrosion coating. The self-repairing anti-corrosion coating can be widely used in the preparation process of a protective layer on the surface of a metal material with anti-corrosion, anti-fouling and self-repairing properties. The above-mentioned self-repairing coating of the present invention can effectively improve the anti-corrosion performance, anti-fouling performance, self-repairing performance and service life of the protective layer on the surface of the metal material without affecting the mechanical properties and shielding of the original coating system. Its potential application can be extended to various applications of polymer materials, biomedical fields and electronic intelligent materials, providing an effective solution for protective coatings with long life and sustainability.

[0014] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0015] The present invention provides a self-repairing anti-corrosion coating, the self-repairing anti-corrosion coating comprising:

[0016] Two-dimensional nanosheets, polyphenolic bio-based materials, polyolefin alcohols, polymer resins containing active hydrogen atoms, isocyanate curing agents, and dispersion media;

[0017] The polyphenol bio-based material is a bio-based material with hydroxyl groups on the surface and having the activity of complexing reaction with metal ions.

[0018] Furthermore, the self-repairing anti-corrosion coating comprises, by mass percentage:

[0019] Two-dimensional nanosheets 0.004~3%, polyphenol bio-based materials 0.01~3.99%, polyolefin alcohol 0.23~5.03%, polymer resin containing active hydrogen atoms 21.92~45.05%, isocyanate curing agent 24.92~76.92% and the balance dispersion medium.

[0020] Furthermore, the polyphenolic bio-based material includes at least one of tea polyphenols, catechins, tannic acid, and gallic acid.

[0021] Furthermore, the polymer resin containing active hydrogen atoms is a water-insoluble amino or hydroxyl resin that can react with isocyanate;

[0022] Preferably, the active hydrogen equivalent of the polymer resin containing active hydrogen atoms is 200 to 5000;

[0023] Preferably, the polymer resin containing active hydrogen atoms includes at least one of a secondary amino polymer resin, a primary amino polymer resin, a hydroxy acrylic resin, a hydroxy polyether resin, and a polyester resin.

[0024] Furthermore, the two-dimensional nanosheet includes at least one of graphene oxide, reduced graphene oxide, partially reduced graphene oxide, graphene structural derivatives, molybdenum disulfide and its structural derivatives, or layered titanium carbide and its structural derivatives.

[0025] Further, the molecular weight of the polyolefin alcohol is 3000-180000;

[0026] Preferably, the polyolefin alcohol comprises at least one of polyvinyl alcohol 1799, polyvinyl alcohol 1792, polyvinyl alcohol 1788, polyethylene glycol or derivatives thereof.

[0027] Further, the isocyanate curing agent includes at least one of hexamethylene diisocyanate, diphenylmethane diisocyanate, toluene diisocyanate, polyphenylmethane polyisocyanate, naphthalene diisocyanate, polymethylene polyphenyl polyisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate and xylylene diisocyanate.

[0028] The present invention provides a method for preparing a self-repairing anti-corrosion coating, the preparation method comprising:

[0029] (A) preparing a nanosheet hydrosol: mixing two-dimensional nanosheets, polyphenolic bio-based materials and polyolefin alcohol in a dispersion medium, heating and stirring to obtain a bio-based nanosheet hydrosol;

[0030] The nanosheet hydrosol is obtained from two-dimensional nanosheets, polyphenol bio-based materials and polyolefin alcohol;

[0031] (B) Emulsification: adding the nanosheet hydrosol to the polymer resin containing active hydrogen atoms and emulsifying at high speed to obtain emulsion A;

[0032] During high-speed emulsification, due to the difference in surface tension of different droplets, the nanosheet hydrosol forms microspherical droplets in emulsion A;

[0033] (C) Freezing: Freezing the emulsion A to obtain polymer resin A;

[0034] The sol microsphere droplets in the emulsion A are frozen at low temperature to form droplet-shaped solid microspheres in the polymer resin A, and the resin components in the polymer resin A are not affected by the freezing;

[0035] (D) Thawing: The polymer resin A is thawed. After the solid microspheres in the polymer resin A are thawed and melted, the polyolefin alcohol polymer in the microspheres is rearranged and re-crosslinked to form gel microspheres, thereby obtaining a polymer resin B containing active hydrogen atoms and having the gel microspheres uniformly distributed therein.

[0036] (E): Preparation of coating: Mix polymer resin B and isocyanate curing agent to obtain a self-healing anti-corrosion coating.

[0037] Furthermore, the preparation method of step (A) comprises:

[0038] The two-dimensional nanosheets are added to a dispersion medium for ultrasonic dispersion, and then polyphenolic bio-based materials and polyolefin alcohol are added in sequence for mixing, followed by heating and stirring, and cooling to obtain a bio-based nanosheet hydrosol containing sol microspheres;

[0039] Preferably, the ultrasonic dispersion time is 10-100 min and the ultrasonic frequency range is 50-40 kHz;

[0040] Preferably, the temperature of the heating and stirring is 50-99° C., and the time of the heating and stirring is 1-24 hours;

[0041] And / or, in step (B), the speed of high-speed emulsification is 2000-30000 rpm, and the time is 5-30 min;

[0042] And / or, the freezing temperature in step (C) is -80 to 0°C and the freezing time is 0.01 to 100 h;

[0043] And / or, the thawing temperature in step (D) is 0-80°C and the thawing time is 0.01-100 h.

[0044] Application of a self-repairing anti-corrosion coating provided by the present invention in preparing a protective layer on the surface of a metal material;

[0045] Preferably, the metal material surface protective layer has anti-corrosion, anti-fouling and self-repairing properties.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The self-repairing anti-corrosion coating provided by the present invention comprises: two-dimensional nanosheets, polyphenolic bio-based materials, polyolefin alcohol, polymer resin containing active hydrogen atoms, isocyanate curing agent and dispersion medium; wherein: the polyphenolic bio-based materials in the self-repairing coating of the present invention are bio-based materials with hydroxyl groups on the surface and having the activity of complexing reaction with metal ions. The self-repairing anti-corrosion coating prepared from the above raw materials of the present invention has the advantages of simple preparation, high environmental protection, small loss of mechanical properties of the coating, good shielding performance, strong self-repairing performance, and also has good anti-corrosion and anti-fouling performance.

[0048] The present invention provides a method for preparing a self-repairing anti-corrosion coating. The method first uses two-dimensional nanosheets, polyphenol bio-based materials and polyolefin alcohol to prepare a bio-based nanosheet hydrosol; then, under the action of emulsification and freeze-thaw, a polymer resin B containing active hydrogen atoms and gel microspheres uniformly distributed inside is obtained, and then the polymer resin B is mixed with an isocyanate curing agent to obtain a self-repairing anti-corrosion coating.

[0049] The preparation method of the present invention directly adds bio-based nanosheet hydrosol to a solvent-free and water-insoluble polymer resin containing active hydrogen atoms, and uses the difference in surface tension of different droplets through a high-speed emulsification method to form microspherical sol droplets (hydrosol microspheres) in emulsion A; then, the metastable hydrosol microspheres in the mixed resin are converted into relatively stable bio-based hydrogel microspheres through a freeze-thaw method and evenly distributed in the resin, and then mixed with an isocyanate curing agent to obtain a self-repairing anti-corrosion coating. The preparation method of the present invention has the technical advantages of high output rate and simple process compared to the existing conventional self-repairing material preparation method.

[0050] The self-repairing anti-corrosion coating provided by the present invention can be widely used in the preparation process of the surface protective layer of metal materials with anti-corrosion, anti-fouling and self-repairing properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0052] Figure 1 The morphology pictures and XPS spectrum C1s analysis diagram of TGPG gel and polyvinyl alcohol gel in Example 1 provided in Experimental Example 1 of the present invention;

[0053] Figure 2 An optical microscope image of the self-repairing anti-corrosion coating of Example 1 provided in Test Example 1 of the present invention;

[0054] Figure 3 This is an electron scanning microscope image of the cross section of the self-repairing anti-corrosion coating of Example 1 after liquid nitrogen brittle fracture provided in Test Example 1 of the present invention;

[0055] Figure 4 A tensile strength and elongation curve diagram of the self-repairing anti-corrosion coating of Example 1 and the original coating (PAE) provided in Test Example 1 of the present invention;

[0056] Figure 5 A comparison chart of oxygen permeability between the self-repairing anti-corrosion coating of Example 1 and the original coating (PAE) provided in Test Example 1 of the present invention;

[0057] Figure 6 A comparison chart of the salt spray test between the self-repairing anti-corrosion coating of Example 1 and the original coating (PAE) provided in Test Example 1 of the present invention;

[0058] Figure 7 Infrared temperature diagrams of the self-repairing anti-corrosion coating of Example 1 and the original coating (PAE) after 0, 2, 5, and 10 minutes of irradiation with simulated sunlight provided in Test Example 1 of the present invention;

[0059] Figure 8 Optical microscope photographs of the self-repairing anti-corrosion coating of Example 1 provided in Test Example 1 of the present invention before repair and after photothermal repair. DETAILED DESCRIPTION

[0060] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0061] According to one aspect of the present invention, a self-repairing anti-corrosion coating comprises:

[0062] Two-dimensional nanosheets, polyphenolic bio-based materials, polyolefin alcohols, polymer resins containing active hydrogen atoms, isocyanate curing agents, and dispersion media;

[0063] The polyphenol bio-based material is a bio-based material with hydroxyl groups on the surface and having the activity of complexing reaction with metal ions.

[0064] The self-repairing anti-corrosion coating provided by the present invention comprises: two-dimensional nanosheets, polyphenolic bio-based materials, polyolefin alcohol, polymer resin containing active hydrogen atoms, isocyanate curing agent and dispersion medium; wherein: the polyphenolic bio-based materials in the self-repairing coating of the present invention are bio-based materials with hydroxyl groups on the surface and having the activity of complexing reaction with metal ions. The self-repairing anti-corrosion coating prepared from the above raw materials of the present invention has the advantages of high environmental protection, small loss of mechanical properties of the coating, good shielding performance, strong self-repairing performance, and also has good anti-corrosion and anti-fouling properties.

[0065] Specifically, the principle of the self-repairing anti-corrosion coating of the present invention to achieve the above performance is as follows:

[0066] (1) Strong self-healing performance:

[0067] The coating of the invention has excellent light-to-heat conversion performance and self-repairing performance.

[0068] The self-repairing of the coating system of the present invention mainly comes from: the polyphenolic bio-based substances released from the gel, such as tea polyphenols, can form complexes with metal ions as initial corrosion protection;

[0069] For example, the gel microspheres formed by "tea polyphenols @ graphene oxide @ polyvinyl alcohol gel" give the composite coating excellent photothermal conversion properties. Under light conditions, the temperature of the composite coating can be rapidly increased, thereby softening the coating and rewinding the film-forming polymer, further realizing the repair of the coating.

[0070] Specifically, the self-healing performance of the coating of the present invention is achieved in two ways:

[0071] 1. When the paint film breaks, the bio-based gel microspheres also break. When the external aqueous solution penetrates, the polyphenol bio-based materials in the gel microspheres are released and dissolved in the aqueous solution. When they come into contact with the metal substrate, the polyphenol bio-based materials form a relatively stable complex with the metal, preventing further erosion by the external electrolyte, thereby improving the corrosion resistance.

[0072] 2. Since the two-dimensional nanomaterial graphene oxide is reduced simultaneously during the sol preparation process, the gel containing the reduced two-dimensional nanomaterial has enhanced infrared absorption performance; the gel enables the composite coating to have excellent photothermal conversion performance. Under light conditions, it can promote the rapid increase in the temperature of the composite coating, thereby achieving the softening of the coating and the re-winding of the film-forming polymer, and further realizing the repair of the coating.

[0073] (2) Anti-corrosion performance: The coating of the present invention has excellent anti-corrosion performance.

[0074] (3) High environmental protection:

[0075] The present invention adopts bio-based materials such as polyphenol bio-based materials and polyolefin alcohol gel to prepare gel microspheres with anti-corrosion properties. Different from the high pollution of conventional microcapsule preparation materials, the used materials are low-carbon and environmentally friendly. At the same time, the prepared self-healing coating has low volatile organic matter content and high environmental protection.

[0076] (4) High mechanical strength:

[0077] Different from the loss of mechanical properties due to the addition of foreign substances such as microcapsules in conventional self-healing coatings, in the present invention, the surface of the gel microspheres in the coating made of hydroxyl-rich polyolefin alcohol and polyphenolic bio-based materials with hydroxyl groups on the surface and active for complexing reaction with metal ions is rich in active groups such as hydroxyl groups, which can react with the curing agent isocyanate during the film formation process to form in-situ embedding, reducing the phase separation in the microstructure; in addition, the bio-based gel in the present invention also has a fine internal structure containing lamellar nanosheet materials (such as graphene oxide), which improves the structural strength and toughness of the material.

[0078] (5) Good shielding performance. In the present invention, the self-healing coating has excellent anti-corrosion and shielding properties. Usually, due to the introduction of microcapsules, the density of the internal structure of conventional self-healing coatings is weakened. Due to their hydrophilic properties, some capsule materials are more likely to cause anti-corrosion weak points in the coating, and the shielding performance of the coating is weakened. The gel microsphere material in the present invention is due to the reduction reaction and in-situ synthesis of two-dimensional nanomaterials (such as graphene) with polyolefin alcohol gel and polyphenol bio-based materials. Through the maze shielding effect of two-dimensional nanomaterials, for example: after the gel microspheres of the present invention are released, the gel microspheres can form a graphene sheet structure, thereby blocking the entry of water molecules, effectively avoiding the above-mentioned defects of existing conventional self-healing coatings, so that the shielding performance and mechanical strength of the coating of the present application are significantly enhanced. In addition, the in-situ embedding of the gel microsphere material in the coating can reduce the oxygen permeability of the coating by several orders of magnitude.

[0079] In a preferred embodiment of the present invention, the self-healing anti-corrosion coating comprises, by mass percentage: 0.004-3% of two-dimensional nanosheets, 0.01-3.99% of polyphenol bio-based materials, 0.23-5.03% of polyolefin alcohol, 21.92-45.05% of polymer resin containing active hydrogen atoms, 24.92-76.92% of isocyanate curing agent and the remainder of dispersion medium.

[0080] Typical but non-limiting preferred embodiments of the above-mentioned two-dimensional nanosheets are: 0.004%, 0.008%, 0.01%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% and 3%.

[0081] Typical but non-limiting preferred embodiments of the above-mentioned polyphenol bio-based materials are: 0.01%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9% and 3.99%.

[0082] Typical but non-limiting preferred embodiments of the above-mentioned polyolefin alcohols are: 0.23%, 0.24%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0% and 5.03%.

[0083] Typical but non-limiting preferred embodiments of the above-mentioned polymer resin containing active hydrogen atoms are: 21.92%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 44%, 44%, 45% and 45.05%.

[0084] Typical but non-limiting preferred embodiments of the above-mentioned isocyanate curing agent are: 24.92%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 44%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 55%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 66%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 77%, 74%, 75%, 76% and 76.92%.

[0085] In a preferred embodiment of the present invention, the polyphenolic bio-based material includes at least one of tea polyphenols, catechins, tannic acid and gallic acid.

[0086] In the above preferred embodiment, non-limiting examples of the polyphenolic bio-based materials are catechins, flavonoids, anthocyanins, tannic acid, gallic acid, epicatechin (EC), epigallocatechin (EGC), epicatechin gallate (ECG) and epigallocatechin gallate (EGCG). Among them, any one or more of gallocatechin (GC), epigallocatechin (EGC), epigallocatechin gallate (EGCG), epicatechin (EC) and epicatechin gallate.

[0087] In a preferred embodiment of the present invention, the polymer resin containing active hydrogen atoms is a water-insoluble amino or hydroxyl resin that can react with isocyanate;

[0088] In the above preferred embodiment, the active hydrogen equivalent of the polymer resin containing active hydrogen atoms is 200-5000.

[0089] Preferably, the polymer resin containing active hydrogen atoms includes at least one of a secondary amino polymer resin, a primary amino polymer resin, a hydroxy acrylic resin, a hydroxy polyether resin, and a polyester resin.

[0090] More preferably, the polymer resin containing active hydrogen atoms is a low-viscosity, water-insoluble polyaspartic acid ester resin with secondary amino groups, and the equivalent weight of the amino group is 200 to 2000;

[0091] Alternatively, the polymer resin containing active hydrogen atoms is a high solid content, water-insoluble polymer resin with hydroxyl groups, and the equivalent weight of the hydroxyl groups is 200-5000.

[0092] In a preferred embodiment of the present invention, the two-dimensional nanosheets include at least one of graphene oxide, reduced graphene oxide, partially reduced graphene oxide, graphene structural derivatives, molybdenum disulfide and its structural derivatives, or layered titanium carbide and its structural derivatives.

[0093] In a preferred embodiment of the present invention, the molecular weight of the polyolefin alcohol is 3000-180000;

[0094] Preferably, the polyolefin alcohol comprises polyvinyl alcohol 1799, with alcoholysis degree of 98-99%; polyvinyl alcohol 1792, with alcoholysis degree of 91.0-93.0%; polyvinyl alcohol 1788, with alcoholysis degree of 87.0-89.0%; or at least one of polyethylene glycol or its derivatives.

[0095] In a preferred embodiment of the present invention, the isocyanate curing agent includes at least one of hexamethylene diisocyanate, diphenylmethane diisocyanate, toluene diisocyanate, polyphenylmethane polyisocyanate, naphthalene diisocyanate, polymethylene polyphenyl polyisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate and xylylene diisocyanate.

[0096] According to one aspect of the present invention, a method for preparing a self-repairing anti-corrosion coating comprises:

[0097] (A) preparing a nanosheet hydrosol: mixing two-dimensional nanosheets, polyphenolic bio-based materials and polyolefin alcohol in a dispersion medium, heating and stirring to obtain a bio-based nanosheet hydrosol;

[0098] The nanosheet hydrosol is obtained from two-dimensional nanosheets, polyphenol bio-based materials and polyolefin alcohol;

[0099] (B) Emulsification: adding the nanosheet hydrosol to the polymer resin containing active hydrogen atoms and emulsifying at high speed to obtain emulsion A;

[0100] During high-speed emulsification, due to the difference in surface tension of different droplets, the nanosheet hydrosol forms microspherical droplets in emulsion A;

[0101] (C) Freezing: Freezing the emulsion A to obtain polymer resin A;

[0102] The sol microsphere droplets in the emulsion A are frozen at low temperature in the polymer resin A to form droplet-shaped semi-solid microspheres, and the resin components in the polymer resin A are not affected by the freezing;

[0103] (D) Thawing: The polymer resin A is thawed. After the semi-solid microspheres in the polymer resin A are thawed and melted, the polyolefin alcohol polymers in the microspheres are rearranged and re-crosslinked to form gel microspheres, thereby obtaining a polymer resin B containing active hydrogen atoms and having gel microspheres uniformly distributed therein.

[0104] (E): Preparation of coating: Mix polymer resin B and isocyanate curing agent to obtain a self-healing anti-corrosion coating.

[0105] The present invention provides a method for preparing a self-repairing anti-corrosion coating. The method first uses two-dimensional nanosheets, polyphenol bio-based materials and polyolefin alcohol to prepare a bio-based nanosheet hydrosol containing sol microspheres; then, under the action of emulsification and freeze-thaw, a polymer resin B containing active hydrogen atoms and gel microspheres uniformly distributed inside is obtained, and then the polymer resin B is mixed with an isocyanate curing agent to obtain a self-repairing anti-corrosion coating.

[0106] The preparation method of the present invention directly adds bio-based nanosheet hydrosol to a solvent-free and water-insoluble polymer resin containing active hydrogen atoms, and uses the difference in surface tension of different droplets through a high-speed emulsification method to form microspherical sol droplets (hydrosol microspheres) in emulsion A; then, the metastable hydrosol microspheres in the mixed resin are converted into relatively stable bio-based hydrogel microspheres through a freeze-thaw method and evenly distributed in the resin, and then mixed with an isocyanate curing agent to obtain a self-repairing anti-corrosion coating. The preparation method of the present invention has the technical advantages of high output rate and simple process compared to the existing conventional self-repairing material preparation method.

[0107] In a preferred embodiment of the present invention, the method for preparing the gel microspheres in step S1 comprises:

[0108] The two-dimensional nanosheets are added to a dispersion medium for ultrasonic dispersion, and then polyphenolic bio-based materials and polyolefin alcohol are added in sequence for uniform mixing, followed by heating and stirring, and then cooling to obtain a bio-based nanosheet hydrosol;

[0109] Preferably, the ultrasonic dispersion time is 10-100 min and the ultrasonic frequency range is 50-40 kHz;

[0110] Preferably, the temperature of the heating and stirring is 50-99° C., and the time of the heating and stirring is 1-24 hours;

[0111] In a preferred embodiment of the present invention, the speed of the high-speed emulsification is 2000-30000 rpm, and the time is 5-30 min;

[0112] And / or, the freezing temperature in step (C) is -80 to 0°C and the freezing time is 0.01 to 100 h;

[0113] And / or, the thawing temperature in step (D) is 0-80°C and the thawing time is 0.01-100 h.

[0114] Preferably, the method for preparing the self-repairing anti-corrosion coating comprises:

[0115] (1) In a clean three-necked flask, add deionized water and two-dimensional nanosheets, stir evenly, disperse by ultrasonication, then add polyphenol bio-based materials and water, stir evenly for a period of time, add polyolefin alcohol, heat and stir, and cool to room temperature to obtain a bio-based nanosheet hydrosol;

[0116] (2) adding the bio-based nanosheet hydrosol to the polymer resin containing active hydrogen atoms, dispersing in an ultra-high speed disperser to form a white emulsion, placing the white emulsion in a refrigerator for a certain period of time after dispersion, and then taking it out and returning it to room temperature to obtain a polymer resin component A containing bio-based nanosheet gel microspheres;

[0117] (3) Add isocyanate curing agent to the polymer resin component A containing gel microspheres, stir and mix evenly, and apply it on the metal surface to prepare a self-repairing anti-corrosion coating.

[0118] More preferably, the method for preparing the self-repairing anti-corrosion coating comprises:

[0119] (1) In a clean three-necked flask, add deionized water and 0.01-3 wt% of two-dimensional nanosheets and stir evenly, then ultrasonically disperse for 10-100 minutes, then add 0.01-4 wt% of polyphenol bio-based materials, stir for 10-100 minutes, then add 0.24-5 wt% of polyolefin alcohol, heat to 50-99 °C, heat and stir for 1-24 h, and cool to room temperature to obtain a bio-based nanosheet hydrosol;

[0120] (2) adding the bio-based nanosheet hydrosol to 22-75 wt% of a polymer resin containing active hydrogen atoms in proportion, dispersing the mixture in an ultra-high speed disperser for 5-30 minutes to form a white emulsion, and placing the white emulsion in a -5-20°C refrigerator for 1-48 hours after dispersion, and then taking the mixture out and returning it to room temperature to obtain a polymer resin component A containing bio-based nanosheet gel microspheres;

[0121] (3) Add 25-77 wt % of isocyanate curing agent to the polymer resin component A containing bio-based nanosheet gel microspheres, stir and mix evenly, and apply it on the metal surface to prepare a self-healing anti-corrosion coating.

[0122] According to one aspect of the present invention, a self-repairing anti-corrosion coating is used in preparing a protective layer on the surface of a metal material;

[0123] Preferably, the metal material surface protective layer has anti-corrosion, anti-fouling and self-repairing properties.

[0124] The self-repairing anti-corrosion coating provided by the present invention can be widely used in the preparation process of the surface protective layer of metal materials with anti-corrosion, anti-fouling and self-repairing properties.

[0125] The technical solution of the present invention will be further described below in conjunction with embodiments.

[0126] Example 1

[0127] A self-repairing anti-corrosion coating, wherein the self-repairing anti-corrosion coating comprises, by mass percentage:

[0128]

[0129] The preparation method of the self-repairing coating comprises:

[0130] (1) In a clean three-necked flask, add 42.5 g of deionized water and 50 mg of graphene oxide, stir evenly, and then ultrasonically disperse for 30 minutes. Then add 0.55 g of tea polyphenols and 46.9 g of water. After stirring at medium speed for 30 minutes, add 10 g of polyvinyl alcohol 1799, heat to 95 °C, stir for 2 h, and cool to room temperature to obtain a dark brown bio-based nanosheet hydrosol containing sol microspheres.

[0131] The bio-based nanosheet hydrosol containing sol microspheres is tea polyphenols@graphene oxide@polyvinyl alcohol hydrosol (TGPG for short);

[0132] The ultrasonic frequency range of the ultrasonic dispersion is 50~40kHz;

[0133] (2) Adding tea polyphenols @ graphene oxide @ polyvinyl alcohol hydrosol at a ratio of 20% to high solid polyaspartic acid ester resin, emulsifying and dispersing in an ultra-high speed disperser for 15 minutes to form a white emulsion. After the dispersion is completed, the white emulsion is placed in a -15°C refrigerator for 16 hours, and then taken out and returned to room temperature to obtain polyaspartic acid ester resin component A containing tea polyphenols @ graphene oxide @ polyvinyl alcohol gel;

[0134] The rotation speed of the emulsification dispersion is 2000~30000rpm.

[0135] (3) The polyaspartic acid ester resin component A (500 g) containing 20 wt% tea polyphenols @ graphene oxide @ polyvinyl alcohol gel was stirred and mixed with an isocyanate curing agent (hexamethylene diisocyanate, 750 g) in a mass ratio of 2:3, and coated on the metal surface to prepare a tea polyphenols @ graphene oxide @ polyvinyl alcohol gel / polyaspartic acid ester (TGPG / PAE) composite coating.

[0136] Example 2

[0137] A self-repairing anti-corrosion coating,

[0138] Measured by mass percentage, the self-repairing anti-corrosion coating comprises:

[0139]

[0140] The preparation method of the self-repairing coating comprises:

[0141] (1) In a clean three-necked flask, add 30 g of deionized water and 0.83 g of partially reduced graphene oxide, stir evenly, and then ultrasonically disperse for 10 minutes. Then add 0.83 g of catechin and 48.34 g of water. After stirring at medium speed for 100 minutes, add 20 g of polyvinyl alcohol 1788, heat to 50 ° C, stir for 24 hours, and cool to room temperature to obtain a brown bio-based nanosheet hydrosol containing sol microspheres;

[0142] The bio-based nanosheet hydrosol containing sol microspheres is catechin@graphene oxide@polyvinyl alcohol hydrosol;

[0143] The ultrasonic frequency range of the ultrasonic dispersion is 50~40kHz;

[0144] (2) Add the above-mentioned catechin @ graphene oxide @ polyvinyl alcohol hydrosol at a ratio of 5% to high solid polyaspartic acid ester resin (1900 g), emulsify and disperse in an ultra-high speed disperser for 5 minutes to form a white emulsion. After the dispersion is completed, the white emulsion is placed in a -5°C refrigerator for 48 hours, and then taken out and returned to room temperature to obtain polyaspartic acid ester resin component A containing catechin @ graphene oxide @ polyvinyl alcohol gel;

[0145] The rotation speed of the emulsification dispersion is 2000~30000rpm.

[0146] (3) The polyaspartic acid ester resin component A (2000 g) containing 5 wt% catechin @ graphene oxide @ polyvinyl alcohol gel was stirred and mixed with an isocyanate curing agent (diphenylmethane diisocyanate, 6666 g) in a mass ratio of 0.3:1, and coated on a metal surface to prepare a catechin @ graphene oxide @ polyvinyl alcohol gel / polyaspartic acid ester composite coating.

[0147] Example 3

[0148] A self-repairing anti-corrosion coating, wherein the self-repairing anti-corrosion coating comprises, by mass percentage:

[0149]

[0150] The preparation method of the self-repairing coating comprises:

[0151] (1) In a clean three-necked flask, add 40 g of deionized water and 10 g of nano-molybdenum disulfide and stir evenly, then ultrasonically disperse for 100 minutes, then add 13.3 g of tannic acid and 28.7 g of water, stir at medium speed for 10 minutes, then add 8 g of polyvinyl alcohol 1792, heat to 99 °C and stir for 1 h, and cool to room temperature to obtain a dark brown bio-based nanosheet hydrosol containing sol microspheres;

[0152] The bio-based nanosheet hydrosol containing sol microspheres is tannic acid@molybdenum disulfide@polyvinyl alcohol hydrosol;

[0153] The ultrasonic frequency range of the ultrasonic dispersion is 50~40kHz;

[0154] (2) Add the above-mentioned tannic acid @ molybdenum disulfide @ polyvinyl alcohol hydrosol at a ratio of 40% to a high-solid hydroxy acrylic resin (150 g), emulsify and disperse in an ultra-high-speed disperser for 30 minutes to form a white emulsion. After the dispersion is completed, place the white emulsion in a -20°C refrigerator for 1 hour, take it out and return it to room temperature, thereby obtaining a hydroxy acrylic resin component A containing tannic acid @ molybdenum disulfide @ polyvinyl alcohol gel;

[0155] The rotation speed of the emulsification dispersion is 2000~30000rpm.

[0156] (3) Component A of the hydroxyl acrylic resin (250 g) containing 40 wt% of tannic acid@molybdenum disulfide@polyvinyl alcohol gel was stirred and mixed with an isocyanate curing agent (dicyclohexylmethane diisocyanate, 83 g) in a mass ratio of 3:1, and then coated on a metal surface to prepare a tannic acid@molybdenum disulfide@polyvinyl alcohol gel / polyurethane composite coating.

[0157] Example 4

[0158] A self-repairing anti-corrosion coating, wherein the self-repairing anti-corrosion coating comprises, by mass percentage:

[0159]

[0160] The preparation method of the self-repairing coating comprises:

[0161] (1) In a clean three-necked flask, add 19.4 g of deionized water and 0.5 g of graphene oxide, stir evenly, and then ultrasonically disperse for 30 minutes. Then, add 3 g of gallic acid and 30 g of water, stir at medium speed for 60 minutes, then add 25 g of polyvinyl alcohol, heat to 90 °C and stir for 4 h. After cooling to room temperature, a dark brown bio-based nanosheet hydrosol containing sol microspheres is obtained.

[0162] The bio-based nanosheet hydrosol containing sol microspheres is gallic acid@graphene oxide@polyvinyl alcohol hydrosol;

[0163] The ultrasonic frequency range of the ultrasonic dispersion is 50~40kHz;

[0164] (2) Add the gallic acid @ graphene oxide @ polyvinyl alcohol hydrosol at a ratio of 15% to high solid polyaspartic acid ester resin (567 g), emulsify and disperse in an ultra-high speed disperser for 10 minutes to form a white emulsion. After the dispersion is completed, place the white emulsion in a -15°C refrigerator for 16 hours, take it out and return it to room temperature, thereby obtaining polyaspartic acid ester resin component A containing gallic acid @ graphene oxide @ polyvinyl alcohol gel;

[0165] The rotation speed of the emulsification dispersion is 2000~30000rpm.

[0166] (3) The polyaspartic acid ester resin component A (667 g) containing 15 wt% gallic acid @ graphene oxide @ polyvinyl alcohol gel was stirred and mixed with an isocyanate curing agent (isophorone diisocyanate, 1333 g) in a mass ratio of 0.5:1, and coated on the metal surface to prepare a gallic acid @ graphene oxide @ polyvinyl alcohol gel / polyaspartic acid ester composite coating.

[0167] Example 5

[0168] A self-repairing anti-corrosion coating, wherein the self-repairing anti-corrosion coating comprises, by mass percentage:

[0169]

[0170] The preparation method of the self-repairing coating comprises:

[0171] (1) In a clean three-necked flask, add 18 g of deionized water and 0.2 g of graphene, stir evenly, and then disperse by ultrasonication for 30 minutes. Then, add 1 g of epicatechin and 13.8 g of water, stir at medium speed for 30 minutes, then add 67 g of polyethylene glycol, heat to 85 °C, stir for 12 h, and cool to room temperature to obtain a dark brown bio-based nanosheet hydrosol containing sol microspheres.

[0172] The bio-based nanosheet hydrosol containing sol microspheres is catechin@graphene@polyethylene glycol hydrosol;

[0173] The ultrasonic frequency range of the ultrasonic dispersion is 50~40kHz;

[0174] (2) Add the epicatechin @ graphene @ polyethylene glycol hydrosol at a ratio of 20% to a high solid polyester polyol resin (400 g), emulsify and disperse in an ultra-high speed disperser for 15 minutes to form a white emulsion. After the dispersion is completed, the white emulsion is placed in a -20°C refrigerator for 20 hours, and then taken out and returned to room temperature to obtain a polyester polyol resin component A containing epicatechin @ graphene @ polyethylene glycol gel;

[0175] The rotation speed of the emulsification dispersion is 2000~30000rpm.

[0176] (3) The polyester polyol resin component A (500 g) containing 20 wt% epicatechin@graphene@polyethylene glycol gel was stirred and mixed with an isocyanate curing agent (hexamethylene diisocyanate, 833 g) in a mass ratio of 0.6:1, and coated on the metal surface to prepare an epicatechin@graphene@polyethylene glycol gel / polyurethane composite coating.

[0177] Example 6

[0178] A self-repairing anti-corrosion coating, wherein the self-repairing anti-corrosion coating comprises, by mass percentage:

[0179]

[0180] The preparation method of the self-repairing coating comprises:

[0181] (1) In a clean three-necked flask, add 41 g of deionized water and 0.7 g of nano-titanium carbide and stir evenly, then ultrasonically disperse for 30 minutes, then add 2.3 g of tea polyphenols and 41 g of water, stir at medium speed for 30 minutes, then add 15 g of polyvinyl alcohol, heat to 70 °C and stir for 20 h, and cool to room temperature to obtain a dark gray bio-based nanosheet hydrosol containing sol microspheres;

[0182] The bio-based nanosheet hydrosol containing sol microspheres is tea polyphenols@titanium carbide@polyvinyl alcohol hydrosol;

[0183] The ultrasonic frequency range of the ultrasonic dispersion is 50~40kHz;

[0184] (2) Add the above tea polyphenol @ titanium carbide @ polyvinyl alcohol hydrosol into high solid polyaspartic acid ester resin (900 g) at a ratio of 10%, emulsify and disperse in an ultra-high speed disperser for 10 minutes to form a white emulsion. After the dispersion is completed, place the white emulsion in a -10°C refrigerator for 18 hours, take it out and return it to room temperature, thereby obtaining polyaspartic acid ester resin component A containing tea polyphenol @ titanium carbide @ polyvinyl alcohol gel;

[0185] The rotation speed of the emulsification dispersion is 2000~30000rpm.

[0186] (3) The polyaspartic acid resin component A (1000 g) containing 10 wt% tea polyphenols @ titanium carbide @ polyvinyl alcohol gel was stirred and mixed with an isocyanate curing agent (hexamethylene diisocyanate, 1428 g) in a mass ratio of 0.7:1, and coated on the metal surface to prepare a tea polyphenols @ titanium carbide @ polyvinyl alcohol gel / polyaspartic acid ester composite coating.

[0187] Test Example 1

[0188] The self-repairing coating prepared in Example 1 is taken as an example to test the self-repairing anti-corrosion coating prepared in the present invention.

[0189] Note: In this test example and the accompanying drawings, the self-healing coating prepared in Example 1 is a tea polyphenols @ graphene oxide @ polyvinyl alcohol gel / polyaspartic acid ester (TGPG / PAE) composite coating, referred to as TGPG / PAE.

[0190] The original coating is a coating prepared by uniformly mixing polyaspartic acid ester resin and isocyanate curing agent and coating it on the metal surface, referred to as PAE.

[0191] The preparation method of the original coating comprises: stirring and mixing polyaspartic acid ester resin (500 g) and isocyanate curing agent (hexamethylene diisocyanate, 750 g) in a mass ratio of 2:3, uniformly coating the mixture on a metal surface, and preparing the original coating.

[0192] The specific test results are as follows:

[0193] Figure 1 The morphology pictures and XPS spectrum C1s analysis diagrams of TGPG gel and polyvinyl alcohol gel in Example 1 provided for this experimental example. Figure 1 a is polyvinyl alcohol gel; Figure 1 b is tea polyphenols@graphene oxide@polyvinyl alcohol gel (TGPG); Figure 1 c is the XPS spectrum C1s analysis diagram of PG; Figure 1 d is the XPS spectrum C1s analysis diagram of TGPG.

[0194] See also Figure 1 a and Figure 1 b, polyvinyl alcohol gel is colorless, transparent and has very low strength, TPG is yellow-brown, while TGPG has higher strength, has the smallest deformation under external force compression, and the gel is black;

[0195] See also Figure 1c, PG has four characteristic binding energies, namely CC (284.8 eV), C-OH (286.3 eV), OC=O (288.6 eV), and CH (285.9 eV). In contrast, Figure 1 The C1s spectrum of TGPG in d shows that C-OH is significantly reduced and a new component C=C (284.2 eV) appears, indicating the successful introduction of aromatic C=C in tea polyphenols and the conjugated structure on the graphene surface.

[0196] Figure 2 Optical microscope image of the self-repairing anti-corrosion coating of Example 1 provided for this test example.

[0197] Depend on Figure 2 It can be seen that the gel microspheres in the coating of Example 1 are in the form of 15-25 micron spheres and are relatively evenly dispersed in the coating film.

[0198] Figure 3 This is an electron scanning microscope image of the cross-section of the self-repairing anti-corrosion coating of Example 1 provided in this test example after liquid nitrogen brittle fracture. Figure 3 a is a 100 μm scale electron scanning microscopy image; Figure 3 b is a 5 μm scale electron scanning micrograph.

[0199] Depend on Figure 3 It can be seen that the gel microspheres are evenly embedded in the coating, and the microspheres and the coating are tightly bound without obvious phase separation.

[0200] Figure 4 The tensile strength and elongation curves of the self-repairing anti-corrosion coating of Example 1 and the original coating (PAE) provided for this test example.

[0201] Depend on Figure 4 It can be seen that after the gel microspheres were added to the coating system, the tensile strength did not decrease significantly, while the elongation increased.

[0202] Figure 5 The oxygen permeability comparison chart of the self-repairing anti-corrosion coating of Example 1 and the original coating (PAE) provided in this test example. Figure 5 It can be seen that the oxygen permeability resistance of the gel composite coating is about one order of magnitude higher than that of the original coating, indicating that the coating has excellent shielding properties;

[0203] Figure 6 The salt spray test comparison chart of the self-repairing anti-corrosion coating of Example 1 and the original coating (PAE) provided for this test example. Figure 6 It can be seen that after 1000 hours of salt spray test, Figure 6 aThe original coating has more rust spots, while Figure 6b The gel composite coating provided by the present invention has few rust spots on the surface, indicating that the gel composite coating has excellent anti-corrosion performance.

[0204] Figure 7 Infrared temperature diagrams of the self-repairing anti-corrosion coating of Example 1 and the original coating (PAE) after 0, 2, 5, and 10 minutes of irradiation with simulated sunlight provided for this test example.

[0205] Figure 7 a1 is the infrared temperature graph of the original coating (PAE) after 0 minutes of exposure to simulated sunlight; Figure 7 a2 is the infrared temperature diagram of the original coating (PAE) after 2 minutes of exposure to simulated sunlight; Figure 7 a3 is the infrared temperature graph of the original coating (PAE) after 5 minutes of exposure to simulated sunlight; Figure 7 a4 is the infrared temperature graph of the original coating (PAE) after 10 minutes of exposure to simulated sunlight;

[0206] Figure 7 b1 is an infrared temperature diagram of the self-repairing anti-corrosion coating (TGPG / PAE) of Example 1 after 0 minutes under simulated sunlight; Figure 7 b2 is an infrared temperature diagram of the self-repairing anti-corrosion coating (TGPG / PAE) of Example 1 after 2 minutes of exposure to simulated sunlight; Figure 7 b3 is an infrared temperature diagram of the self-repairing anti-corrosion coating (TGPG / PAE) of Example 1 after 5 minutes of exposure to simulated sunlight; Figure 7 b4 is an infrared temperature diagram of the self-repairing anti-corrosion coating (TGPG / PAE) of Example 1 after 10 minutes of exposure to simulated sunlight.

[0207] Depend on Figure 7 It can be seen that the surface temperature of the gel composite coating provided by the present invention rises rapidly in the same time, which also shows that the gel composite coating has excellent light-to-heat conversion performance.

[0208] Figure 8 The optical microscope photos of the self-repairing anti-corrosion coating of Example 1 provided in this test example before and after photothermal repair. Figure 8 It can be seen that the gel composite coating can achieve relatively rapid self-repair under simulated sunlight conditions, which also shows that the gel composite coating has excellent self-repair properties.

[0209] In summary, through the above Figures 1 to 8The display shows that the present invention forms gel microspheres in polyaspartic acid ester resin through high-speed emulsification and freeze-thaw effects, and in-situ access to the coating film during the coating curing process to prepare a technical solution with a self-healing coating. The obtained bio-based gel has stable performance and has little effect on the mechanical properties of the original coating system. The sheet shielding effect of graphene oxide in the gel and the corrosion inhibition effect of the sustained-release polyphenol bio-based material delay the penetration of the corrosive medium and improve the anti-corrosion performance of the coating; the prepared composite coating has good self-healing performance under photothermal conditions. This study provides new ideas for the development of other polymer materials, biomedical materials, and electronic intelligent materials.

[0210] Test Example 2

[0211] In order to show that the self-repairing coating of the present invention has the advantages of small loss of mechanical properties of the coating, good shielding performance and strong self-repairing performance, the self-repairing coatings prepared in Examples 1 to 6 are now subjected to performance verification. The specific performance test results are shown in Tables 1 and 2:

[0212] Table 1:

[0213]

[0214] Table 2:

[0215]

[0216] It can be seen from the above experimental results that the self-repairing coatings prepared in Examples 1 to 6 of the present invention have the advantages of small loss of mechanical properties of the coating, good shielding performance, and strong self-repairing performance.

[0217] Comparative Example 1

[0218] A self-repairing anti-corrosion coating, wherein the self-repairing anti-corrosion coating comprises, by mass percentage:

[0219]

[0220] The preparation method of the self-repairing coating comprises:

[0221] (1) In a clean three-necked flask, add 42.5 g of deionized water and 50 mg of graphene oxide, stir evenly, and then ultrasonically disperse for 30 minutes. Then, add 0.55 g of tea polyphenols and 46.9 g of water, stir at medium speed for 30 minutes, heat to 95 °C, heat and stir for 2 hours, and cool to room temperature to obtain a dark brown bio-based nanosheet hydrosol containing sol microspheres;

[0222] The ultrasonic frequency range of the ultrasonic dispersion is 50~40kHz;

[0223] (2) Same as Example 1.

[0224] (3) Same as Example 1.

[0225] The difference between this comparative example and Example 1 is that polyolefin alcohol is not included in the preparation process of the bio-based nanosheet hydrosol.

[0226] Comparative Example 2

[0227] A self-repairing anti-corrosion coating, the components of the self-repairing anti-corrosion coating are the same as those in Example 1.

[0228] The preparation method of the self-repairing coating comprises:

[0229] (1) In a clean three-necked flask, add 42.5 g of deionized water and 50 mg of graphene oxide, stir evenly, and then ultrasonically disperse for 30 minutes. Then, add 0.55 g of tea polyphenols and 46.9 g of water, stir at medium speed for 30 minutes, then add 10 g of polyvinyl alcohol 1799 and stir at room temperature for 2 hours to obtain a dark brown bio-based nanosheet hydrosol containing sol microspheres;

[0230] The ultrasonic frequency range of the ultrasonic dispersion is 50~40kHz;

[0231] (2) Same as Example 1.

[0232] (3) Same as Example 1.

[0233] The difference between this comparative example and Example 1 is that: step (1) in the preparation process of the bio-based nanosheet hydrosol does not include the step of heating and stirring, and the preparation is carried out at room temperature.

[0234] Comparative Example 3

[0235] A self-repairing anti-corrosion coating, wherein the self-repairing anti-corrosion coating comprises, by mass percentage:

[0236]

[0237] The difference between this comparative example and Example 1 in component composition is that "graphene oxide" is replaced by "mesoporous silica", "tea polyphenols" is replaced by "gallic acid", and "polyvinyl alcohol type 1799" is replaced by "chitosan".

[0238] The preparation method of the self-repairing coating in this comparative example is carried out according to the preparation method of Example 1 using the replaced raw materials.

[0239] Comparative Example 4

[0240] A self-repairing anti-corrosion coating, wherein the self-repairing anti-corrosion coating comprises, by mass percentage:

[0241]

[0242] The difference between this comparative example and Example 1 in component composition is that "graphene oxide" is replaced by "mesoporous silica", "tea polyphenols" is replaced by "tannic acid", and "polyvinyl alcohol type 1799" is replaced by "Eudragit E100".

[0243] The preparation method of the self-repairing coating in this comparative example is carried out according to the preparation method of Example 1 using the replaced raw materials.

[0244] Comparative Example 5

[0245] A self-repairing anti-corrosion coating, wherein the self-repairing anti-corrosion coating comprises, by mass percentage:

[0246]

[0247] The preparation method of the self-repairing coating is the same as that of Example 1.

[0248] In this comparative example, the content of polyolefin alcohol in the self-repairing anti-corrosion coating is greater than 0.23-5.03%.

[0249] Comparative Example 6

[0250] A self-repairing anti-corrosion coating, wherein the self-repairing anti-corrosion coating comprises, by mass percentage:

[0251]

[0252] The preparation method of the self-repairing coating is the same as that of Example 1.

[0253] In this comparative example, the content of the two-dimensional nanosheets in the self-repairing anti-corrosion coating is greater than 0.004-3%.

[0254] Comparative Example 7

[0255] A self-repairing anti-corrosion coating, wherein the self-repairing anti-corrosion coating comprises, by mass percentage:

[0256]

[0257] The preparation method of the self-repairing coating is the same as that of Example 1.

[0258] In this comparative example, the content of polyphenol bio-based materials in the prepared components is greater than 0.01-3.99%.

[0259] Test Example 3

[0260] In order to show that the self-repairing coating of the present invention has the advantages of small loss of mechanical properties of the coating, good shielding performance and strong self-repairing performance, the performance of the self-repairing coatings prepared in Comparative Examples 1 to 7 is verified and compared with Example 1.

[0261] The specific performance test results are shown in Table 3 and Table 4:

[0262] Table 3:

[0263]

[0264] Table 4:

[0265]

[0266] From the above, it can be seen that in Comparative Example 1, since polyolefin alcohol is not included in the preparation process of the bio-based nanosheet hydrosol, bubbles exist in the paint film, the strength and elongation are significantly reduced, the oxygen permeability is increased, the anti-corrosion performance is significantly reduced, and self-repair of scratches cannot be achieved.

[0267] In Comparative Example 2, since the preparation process of the bio-based nanosheet hydrosol does not include the step of heating and stirring, there are particles and some bubbles in the paint film, the strength and elongation are significantly reduced, the oxygen permeability is increased, the anti-corrosion performance is significantly reduced, and self-repair of scratches cannot be achieved.

[0268] In Comparative Examples 3 and 4, due to the different raw material selection during the preparation of the bio-based nanosheet hydrosol, the strength and elongation of the paint film were significantly reduced, the oxygen permeability was also significantly increased, the anti-corrosion performance was reduced by half, and self-repair of scratches could not be achieved.

[0269] In Comparative Examples 5 to 7, since the contents of some components in the preparation process of the bio-based nanosheet hydrosol are not within the range of Examples 1 to 6, the paint film strength is reduced, the oxygen permeability is high, and the anti-corrosion performance is reduced by about 30%.

[0270] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A self-repairing anti-corrosion coating, characterized in that: The self-repairing anti-corrosion coating comprises: 0.004~3% of two-dimensional nanosheets, 0.01~3.99% of polyphenolic bio-based materials, 0.23~5.03% of polyolefin alcohol, 21.92~45.05% of polymer resin containing active hydrogen atoms, 24.92~76.92% of isocyanate curing agent and the balance of dispersion medium; The polyphenolic bio-based material is a bio-based material with hydroxyl groups on the surface and having the activity of complexing with metal ions, including at least one of tea polyphenols, catechins, tannic acid, and gallic acid; The polymer resin containing active hydrogen atoms is an amino or hydroxyl resin that is water-insoluble and can react with isocyanate; The two-dimensional nanosheets include at least one of graphene oxide and partially reduced graphene oxide; The polyolefin alcohol comprises at least one of polyvinyl alcohol 1799, polyvinyl alcohol 1792, polyvinyl alcohol 1788, polyethylene glycol or a derivative thereof; The preparation method of the self-repairing anti-corrosion coating comprises: (A) Preparation of sol microspheres: two-dimensional nanosheets, polyphenolic bio-based materials and polyolefin alcohol are mixed in a dispersion medium, heated and stirred to obtain nanosheet hydrosol; (B) emulsification: adding the nanosheet hydrosol to a polymer resin containing active hydrogen atoms for emulsification to obtain an emulsion A; (C) Freezing: Freezing the emulsion A to obtain polymer resin A; (D) Thawing: Thawing the polymer resin A to obtain a polymer resin B containing active hydrogen atoms and having gel microspheres uniformly distributed therein; (E): Preparation of coating: Mix polymer resin B and isocyanate curing agent to obtain a self-healing anti-corrosion coating.

2. The self-repairing anti-corrosion coating according to claim 1, characterized in that: The active hydrogen equivalent of the polymer resin containing active hydrogen atoms is 200-5000.

3. The self-repairing anti-corrosion coating according to claim 1, characterized in that: The polymer resin containing active hydrogen atoms includes at least one of a secondary amino polymer resin, a primary amino polymer resin, a hydroxy acrylic resin, a hydroxy polyether resin, and a polyester resin.

4. The self-repairing anti-corrosion coating according to claim 1, characterized in that: The molecular weight of the polyolefin alcohol is 3000-180000.

5. The self-repairing anti-corrosion coating according to claim 1, characterized in that: The isocyanate curing agent includes at least one of hexamethylene diisocyanate, diphenylmethane diisocyanate, toluene diisocyanate, polyphenylmethane polyisocyanate, naphthalene diisocyanate, polymethylene polyphenyl polyisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate and xylylene diisocyanate.

6. The self-repairing anti-corrosion coating according to claim 1, characterized in that: The preparation method of step (A) comprises: The two-dimensional nanosheets are added to the dispersion medium for ultrasonic dispersion, and then the polyphenol bio-based materials and polyolefin alcohol are added in sequence and mixed, followed by heating and stirring, and then cooling to obtain the bio-based nanosheet hydrosol.

7. The self-repairing anti-corrosion coating according to claim 6, characterized in that: The ultrasonic dispersion time is 10-100 min, and the ultrasonic frequency range is 50-40 kHz.

8. The self-repairing anti-corrosion coating according to claim 6, characterized in that: The temperature of the heating and stirring is 50-99° C., and the time of the heating and stirring is 1-24 hours.

9. The self-repairing anti-corrosion coating according to claim 1, characterized in that: In step (B), the emulsification speed is 2000-30000 rpm, and the time is 5-30 min.

10. The self-repairing anti-corrosion coating according to claim 1, characterized in that: The freezing temperature in step (C) is -80~0°C and the freezing time is 0.01~100h.

11. The self-repairing anti-corrosion coating according to claim 1, characterized in that: The thawing temperature in step (D) is 0-80°C and the thawing time is 0.01-100h.

12. Use of the self-repairing anti-corrosion coating according to any one of claims 1 to 11 in preparing a surface protective layer for metal materials.

13. The use according to claim 12, characterized in that: The metal material surface protective layer is a metal material surface protective layer with anti-corrosion, anti-fouling and self-repairing properties.

Citation Information

Patent Citations

  • Graphene-based microcapsule and preparation method thereof

    CN118256107A

  • Self-healing waterborne polyurethane with anti-corrosion function and preparation method of self-healing waterborne polyurethane

    CN118290693A